Nhận xét kết quả hóa trị bổ trợ phác đồ 4AC-4T kết hợp Anastrozole cho bệnh nhân ung thư vú ER dương tính/Her2 âm tính giai đoạn II-III - Le, Huy Trinh (2025)
Chemotherapy regimen 4AC-4T (Anthracycline- Cyclophosphamide/Taxane) and Anastrozole are considered to have a significant role in the adjuvant treatment of stage II-III estrogen receptor-positive breast cancer. In this study, the authors used a combination of cross-sectional, retrospective, and prospective study designs on 95 estrogen receptor-positive and Her2 receptor negative stage II-III cancer patients treated at the Hanoi Oncology Hospital from January 1, 2015, to January 1, 2020. The research aims to evaluate the results of treatment of hormone receptor-positive breast cancer with adjuvant chemotherapy regimen 4AC-4T combined with Anastrozole. Results showed that DFS (disease-free survival) rates of 1, 2, 3, 4, and 5 years were 100, 99, 94.1, 88.3, and 88.3%, respectively. OS (overall survival) rates at 2, 3, 4, and 5 years were respectively: 100, 98.1, 95.9, and 95.9%. There was a statistically significant correlation between DFS and lymph node metastasis; between stages II and III. This study exhibited that 4AC-4T and Anastrozole are effective chemotherapeutic regimens for hormone receptor-positive breast cancer.